Carbon capture and sequestration - Hashim, Haslenda (Penerbit UTM, 2008)
In this chapter, a general overview of CO2 capture technologies and sequestration will be presented. CO2 capture and storage process has been viewed as a potential solution to achieve deep reduction of CO2 from power plant flue gas. The goal of CO2 capture technology is to separate the CO2 from its sources in appropriate forms for transportation and sequestration. Once CO2 is captured, it needs to be pipelines and stored securely and permanently. Therefore, the applicability of CO2 capture technologies to power plants must be evaluated in a context of the total system including capture, transportation and storage.